1992
DOI: 10.1007/bf02783996
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium level in patients with colorectal cancer

Abstract: Serum selenium levels were determined by fluorometric procedure in 37 patients of both sexes suffering from colorectal cancer. The diagnosis was verified with histopathological examination during surgical treatment. The values found were 46.8 +/- 11.2 micrograms/L. The control group consisted of 230 healthy persons from the same environment as the group of patients. The values found were 64.2 +/- 11.5 micrograms/L. The results of this study are compared with the results of the other research groups analyzing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Epidemiological studies on individual dietary antioxidants such as vitamins and minerals and the risk of CRC have been conducted previously and produced inconsistent results 10‐31 . Randomized clinical trials evaluating the antioxidant supplementation did not yield consistent data in support of the protective effect against the development of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies on individual dietary antioxidants such as vitamins and minerals and the risk of CRC have been conducted previously and produced inconsistent results 10‐31 . Randomized clinical trials evaluating the antioxidant supplementation did not yield consistent data in support of the protective effect against the development of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for this modification was based on the observation that organoselenium compounds have been shown to be effective in retarding tumorigenesis of several cancer types, including colon cancer (38–42), in both animal models and epidemiological studies. In addition, it has been demonstrated that most cancer patients, including colon cancer patients (43, 44), have lower serum selenium levels than healthy controls. Hence, ISC compounds combined the anticancer properties of both selenium and ITCs.…”
Section: Introductionmentioning
confidence: 99%
“…Certain selenium-based compounds can selectively kill ALL cells by inducing cell cycle arrest and ROS-mediated apoptosis through the mitochondrial signaling pathway. In conclusion, it is clear that the serum selenium level in ALL patients decreases, and the efficacy of appropriate treatment methods may also be related to the increase in selenium level ( Mikac-Dević et al, 1990 ; Wu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%